Antarctic tourism management and regulation: the need for change. (1st May 2013) - Verbitsky, Jane
ABSTRACT Antarctic tourism has experienced a boom period over the last thirty years. Beginning in the 1980s, the number of tourists who visited the continent annually began to rise sharply, and within the space of twenty years the numbers had increased by more than six hundred percent. Despite a global recession and downturn in visitor numbers over the last two austral seasons, the expectation is that Antarctic tourist numbers will trend upward again as the world tourism market recovers and the demand for Antarctic visits increases. In a continent renowned both as the last great global wilderness and as a place dedicated to scientific research in the interests of humankind, tourism on this scale presents a formidable range of issues for the Antarctic Treaty Consultative Parties (ATCPs) to contend with. This article suggests that the rapid growth in Antarctic tourism, and the impacts of that tourism coupled with the lack of a comprehensive regulatory and management framework for tourism now pose a considerable challenge to both the Consultative Parties and to the Antarctic Treaty System (ATS) itself. The obligations and duties of the ATCPs under the Antarctic Treaty and other ATS instruments require a robust, strategic response by them to the issues and concerns generated by the growth of tourism. What is needed, it is argued, is for the parties to initiate a more interventionist pro-active policy approach to create a holistic, binding tourism framework so that they may fulfill more effectively their stewardship and governance roles in Antarctica, prevent degradation of Antarctica's environment, and reduce risks to tourists themselves.